Factors affecting risk management in industrial companies in Jordan - Nadia Abu Kwaik; Rateb J. Sweis; Baraa Allan; Ghaleb Sweis (Administrative Sciences, 2023)
This study aims to identify and rank the critical factors affecting risk management from the perspective of top and Lower Management in Jordanian industrial companies. Based on a rigorous literature review, critical factors affecting risk management are factors related to (1) flexibility and adaptation in the economic environment; (2) company characteristics; (3) external audit quality; (4) government rules and regulations; (5) top management and the board of directors; (6) organizational structure; (7) internal audit effectiveness; (8) trust; (9) human resources efficiency and training (10); communications (11); information technology (12); and the company's culture. Quantitative research methods were used. A questionnaire was developed and distributed to a random sample of senior managers of industrial companies in Jordan. Kendall and Mann-Whitney tests, RII, and EFA were used to analyze the acquired data. The results show that all discussed factors have an effect on risk management, and there is no difference between top and Lower Management's opinions regarding the ranking of the importance of those factors on risk management. This study provides an original perspective on the concept of risk management and the factors that impact it. These findings have important implications for Jordanian industrial companies' decision makers. Companies should apply the results to their strategies and policies to reduce risks.
Keywords: 350; performance; factors affecting risk management; industrial companies; risk management; top and Lower Management